INFLUÊNCIA DA PULVERIZAÇÃO AÉREA DE INSETICIDAS SOBRE O PADRÃO DE DISTRIBUIÇÃO ESPACIAL DE ALABAMA ARGILLACEA (HÜBNER, 1818) E SPODOPTERA FRUGIPERDA (J.E. SMITH, 1797) EM ALGODOEIRO* - Fernandes, M.g.; Maruyama, W.i. [UNESP]; Busoli, A.c. [UNESP]; Barbosa, J.c. [UNESP]; Degrande, P.e. (Instituto Biológico, 2024)
The objective of the research was to determine the effect of the aerial insecticides spraying on the pattern of clumping distribution of the caterpillars Alabama argillacea (Hübner, 1818) and Spodoptera frugiperda (J.E. Smith, 1797) on the cotton crop. The cultivar used was CNPA-ITA 90, with aerial application in four different fields in the area of Ponta Porã’s area, MS, Brazil. The aerial application of insecticides did not alter significantly the pattern of aggregated distribution of the caterpillars of both species significantly, affecting more the population density of little and large larvae, but the population density of the medium larvae was low affected.

O objetivo da pesquisa foi determinar o efeito da pulverização aérea de inseticidas sobre o padrão de distribuição espacial das lagartas Alabama argillacea (Hübner, 1818) e Spodoptera frugiperda (J.E. Smith, 1797) na cultura do algodoeiro cultivar CNPA-ITA 90, em quatro campos diferentes na região de Ponta Porã, MS, Brasil. As pulverizações aéreas de inseticidas não alteraram significativamente o padrão de distribuição espacial agregada de ambas as espécies, interferindo mais sobre a densidade populacional de lagartas pequenas e grandes/planta, sendo que a densidade populacional de lagartas médias foi pouco afetada.
INFLUENCE OF INSECTICIDAL AERIAL SPRAYING ON SPATIAL DISTRIBUTION PATTERN OF ALABAMA ARGILLACEA (HÜBNER, 1818) AND SPODOPTERA FRUGIPERDA (J.E. SMITH, 1797) ON COTTON CROP
Keywords: Insecta; probability distribution; aerial spraying; insecticides; sampling.; Insecta; distribuições de probabilidade; pulverização aérea; inseticidas; amostragem.